2005
DOI: 10.1016/j.jacc.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Increased Vascular Endothelial Growth Factor Expression But Impaired Vascular Endothelial Growth Factor Receptor Signaling in the Myocardium of Type 2 Diabetic Patients With Chronic Coronary Heart Disease

Abstract: Chronic CHD in diabetic patients is characterized by an increased VEGF myocardial expression and a decreased expression of its receptors along with a down-regulation of its signal transduction. The latter could be partially responsible for the reduced neoangiogenesis in diabetic patients with ischemic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
125
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 40 publications
(46 reference statements)
11
125
2
6
Order By: Relevance
“…Sasso et al (19) showed that patients with diabetes had reduced VEGF signaling in the myocardium despite an increase in VEGF ligand (19). We found greater levels of the VEGF ligand with reduced VEGF signaling in hindlimb muscle before ligation, and after ligation this was associated with an impaired perfusion recovery by laser Doppler and a greater extent of tissue necrosis.…”
Section: Discussionsupporting
confidence: 47%
“…Sasso et al (19) showed that patients with diabetes had reduced VEGF signaling in the myocardium despite an increase in VEGF ligand (19). We found greater levels of the VEGF ligand with reduced VEGF signaling in hindlimb muscle before ligation, and after ligation this was associated with an impaired perfusion recovery by laser Doppler and a greater extent of tissue necrosis.…”
Section: Discussionsupporting
confidence: 47%
“…The samples (20 g of protein) were then subjected to heat denaturation at 96°C for 7 min with Laemmli buffer. Western blot analysis for detection of phosphorylated and nonphosphorylated forms of different target molecules was performed according to the method described in previous studies with minor modification (15,18,25,28,45,52). Briefly, each sample was separated on 10% SDS-polyacrylamide gel and transferred to a polyvinylidene difluoride (Millipore, Billerica, MA) membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of protein lysates were obtained as described in previous studies (28,45,52). Protein extracts were incubated overnight at 4°C with 3 g of rabbit polyclonal anti-Flk-1 (Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that without considering the serum VEGF level, the VEGF signaling pathway is impaired during diabetes which is considered as VEGF resistance 28,29 . Therefore, it is possible that reduced serum NO concentration may be responsible for lower neovascularization in hindlimb ischemic tissue of diabetic animals.…”
Section: Discussionmentioning
confidence: 99%